Centro cultural y de artes pardo rubio (2022)
The Pardo Rubio Cultural and Arts Center architectural project proposes to be a center where young people from the town of Chapinero can carry out activities for the development of cultural, artistic, educational and other aspects. This project stems from the lack of cultural facilities in the town of Chapinero compared to the number of inhabitants found there and the little coverage that these spaces offer